Gender Differences in Outcomes of a Healthy Relationships Program to Prevent Intimate Partner Violence. Issue 4 (19th May 2019) - Antle, Becky F.; Barbee, Anita P.; Owen, Jesse; Ness, Erin E.; Minogue, Amanda
Abstract: The purpose was to examine gender differences in the effectiveness of the Within My Reach healthy relationships education program that is an alternative approach to violence prevention. The program was provided to 850 adults in a community-based setting. Baseline, immediate post and six-month follow-up data were collected. There were similar levels of learning, confidence, and communication-and-conflict resolution skill improvement for men and women. Women reported higher levels of satisfaction with the program. Mixed-gender groups reported statistically significant reductions in violence at six-month follow-up. All male groups reported significant increases in violence. Implications are discussed.